Graft-versus-host disease after allogeneic hematopoietic stem cell transplantation in children - Y. V. Skvortsova; D. N. Balashov; V. M. Delyagin (Медицинский совет, 2016)
Up to 60 thousand hematopoietic stem cell transplantations (HSCT) are carried out globally all over the world. The outcome of HSCT is largely determined by the probability and severity of the graft-versus-host reaction/disease (GVHD). Treatment involves corticosteroids. Antithymocyte globulin, extracorporeal photopheresis, monoclonal antibodies to interleukins or their receptors, methotrexate, cyclosporine, tacrolimus, sirolimus, antithymocyte globulin, etc. are used in steroid-refractory GVHD. It is worth to mention that mycophenolate mofetil, esther of mycophenolic acid, blocks proliferation of T and B lymphocytes. In patients who are refractory to corticosteroids, the use of mycophenolate mofetil in isolation or in combination with cyclosporine, tacrolimus seems to be justified.